Kajian Hukum Atas Hubungan Antara Nasabah Dan Bank Ditinjau Dari Undang-Undang Nomor 10 Tahun 1998 Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 Tentang Perbankan - Andriany Widie Astuti; Wahyuni Safitri (Law Department, University of Widya Gama Mahakam Samarinda, 2020)
The relationship between banks and customers is based on the two most related elements, namely law and trust. A bank can only carry out activities and develop its bank, if the community